Complementary effect of combined bacterial-chemical pretreatment to promote enzymatic digestibility of lignocellulose biomass. (January 2019) - Si, Mengying; Liu, Dan; Liu, Mingren; Yan, Xu; Gao, Congjie; Chai, Liyuan; Shi, Yan
Highlights: Significant complementary effect existed in combined bacterial-chemical treatment. The complementary effect overcame the limitation of the chemical treatment. Saccharolytic bacteria enhanced the digestibility of the N-RS by decrystallization. Ligninolytic bacteria enhanced the digestibility of the H-RS by delignification. Abstract: Chemical pretreatment partially modified the structure of lignocellulose to enhance saccharification, leaving unaltered factors to limit further hydrolysis. To overcome these limitations, a biostrategy involving co-pretreatment combining bacteria with a chemical process was developed. A significant complementary effect was observed in specific co-pretreatments, e.g., ligninolytic bacteria enhanced acid pretreatment and saccharolytic bacteria enhanced alkaline pretreatment. Specifically, the ligninolytic bacterium Pandoraea sp. B-6 selectively removed the acidolysis-caused residual lignin and enhanced sugar release by 40.9% to 772.0 mg g −1 compared with that of acid-treated rice straw. After most of the lignin was removed, sugar release from alkali-treated RS was further improved by 31.8% to 820.2 mg g −1 via the saccharolytic bacterium Acinetobacter sp. B-2 through decrystallization. In the complementary mechanism, the active sites produced by chemical cleavage facilitated the bioprocess and further enhanced saccharification. This complementary mechanism provides a novel foundation for designing a rational combination pretreatment.